Interaction of physical activity and interoception in children - Georgiou, Eleana; Matthias, Ellen; Kobel, Susanne; Kettner, Sarah; Dreyhaupt, Jens; Steinacker, Jürgen M.; Pollatos, Olga (Frontiers in Psychology, 2015)
Background: Physical activity (PA) is associated with positive health outcomes, whereas physical inactivity is related to an increased risk for various health issues including obesity and cardiovascular diseases. Previous research indicates that interindividual differences in the perception of bodily processes (interoceptive sensitivity, IS) interact with the degree of PA in adults. Whether there is a similar relationship between PA and IS in children has not been investigated yet. Therefore, the aim of this study was to investigate the interaction between IS and PA during physical performance tasks and in everyday situations. Methods: IS was assessed using a heartbeat perception task in a sample of 49 children within the health promotion program “Join the Healthy Boat” which is implemented in several primary schools in the southwest of Germany. PA was examined using a physical performance task, assessing the distance covered during a standardized 6-minute run. In a subsample of 21 children, everyday PA was measured by a multi-sensor device (Actiheart, CamNtech, Cambridge, UK) during five consecutive days with more than 10 hours of daily data collection. Results: Children with higher IS performed better in the physical performance task. Additionally, based on energy expenditure defined as metabolic equivalents, IS was positively correlated with the extent of light PA levels in the morning and afternoon. Conclusions: Our finding reveal that IS interacts with the degree of PA in children supporting the idea that interoception is important for the self-regulation of health-related behavior.